2008
DOI: 10.1590/s1516-635x2008000300004
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and glucose metabolism of broilers (Gallus gallus domesticus) experimentally infected with Eimeria acervulina Tyzzer, 1929 oocysts

Abstract: Lipid and glucose metabolism of 76 ten-day-old Cobb male broilers, experimentally infected with Eimeria acervulina, was studied for 30 days. Birds were distributed in 2 groups: one infected with 1x10(6) E. acervulina sporulated oocysts, and the other inoculated with distilled water. Pathological e biochemical liver changes were assessed, as well as plasma glucose concentrations and total cholesterol, HDL, LDL, VLDL, fatty-acid, and triglyceride levels in the serum. The infected broilers presented hypoglycemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Serum cholesterol concentration of healthy broilers reported in previous studies ranged between 20 and 200 mg/dl (Qureshi et al 2004;GarciaPerez et al 2005;Kannan et al 2005;Panda et al 2006;Musa et al 2007;Silva et al 2007;Anitha et al 2007;Mashair et al 2007;Freitas et al 2008;Prasad et al 2009). …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Serum cholesterol concentration of healthy broilers reported in previous studies ranged between 20 and 200 mg/dl (Qureshi et al 2004;GarciaPerez et al 2005;Kannan et al 2005;Panda et al 2006;Musa et al 2007;Silva et al 2007;Anitha et al 2007;Mashair et al 2007;Freitas et al 2008;Prasad et al 2009). …”
Section: Discussionmentioning
confidence: 93%
“…These previous studies were aimed at evaluating the relationship between abdominal and serum fat ); comparison of serum lipid profile between breeds (Wang and Musa 2007); effects of some drugs (GarciaPerez et al 2005), vaccines (Talebi 2006), and special diet (Kannan et al 2005;Anitha et al 2007); the effect of age on serum lipids (Silva et al 2007); and to study the effect of some pathogen on serum parameter (Freitas et al 2008). This study has focused on their control groups for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…They may cause death, depending on the animal's state of health and the infecting dose (FREITAS et al, 2008b). The lesions caused by intestinal eimeriosis five rise to disorders of nutrient absorption, thereby triggering changes to carbohydrate, protein, lipid and macro and micronutrient metabolism (TURK et al, 1982;FREITAS et al, 2008a). However, the mechanisms involved in these changes are not totally clear with regard to the post-infection period within which they occur and the repercussion of this infection on the host's weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…The normal plasma values for glucose can be linked to the hepatic glycogenolysis carried out by the bird, in which the glucose is kept at its baseline levels by means of breakdown of hepatic glycogen through glucagon release by the pancreas (RUFF; WILKINS, 1980;FREITAS et al, 2008). According to Chapman et al (1982), the bird's ability to maintain normal blood glucose levels in situations in which the reserves of hepatic glycogen are exhausted is due to gluconeogenesis or reduction of the bird's use of glucose.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that the dosage of E. maxima used caused reductions in lipid absorption. Freitas et al (2008) studied the alterations in the metabolism of broiler chicken experimentally infected with E. acervulina (an enteric parasite), and observed that all classes of lipids in the serum, and lipoproteins, were reduced in infected birds.…”
Section: Discussionmentioning
confidence: 99%